PENGARUH KELUARGA KRISTEN TERHADAP PEMBENTUKAN WATAK REMAJA KRISTEN USIA 12-17 TAHUN GKPI PAGAR BERINGIN KECAMATAN SIPOHOLON 2019 - Hanna Veronika Bako (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
Abstract,This study aims to determine the influence of the Christian family with the formation of the character of adolescents aged 12-17 years in the Church of GKPI Pagar Beringin, Sipoholon Subdistrict, North Tapanuli Regency in 2019. Research Hypothesis is that there is a positive and significant influence of Christian families on the character formation of adolescents aged 12-17 years in the GKPI Church of Pingin Beringin, Sipoholon Subdistrict, North Tapanuli Regency in 2019. This research is a quantitative study using inferential statistical techniques.The population is all adolescents aged 12-17 years in the GKPI Pagar Beringin Church numbering 35 people. The sample is the entire population, thus this study is a population study. The research instrument was a closed questionnaire.Hypothesis testing obtained Fcount = 8.494 Ftable = 2.09 then H0 was rejected and Ha was accepted, namely the positive and significant influence of the Christian family on the formation of the 12-17 year old character. This study concluded that the Christian family had a positive and significant effect on the formation of adolescent characters aged 12 -17 years in the GKPI Church of Pingin Beringin, Sipoholon Subdistrict, North Tapanuli Regency in 2019 by 21.25%.Keywords: Christian Family, Formation of Youth Character